Threshold-dependent tax enforcement and the size distribution of firms: evidence from Germany - Drahomir Klimsa; Robert Ullmann (International Tax and Public Finance, 2022)
This paper investigates firms' responses to threshold-dependent intensity of tax enforcement. We use administrative tax return data over the entire population of German firms and exploit industry variation in firm size thresholds applied by the tax administration. In our setting, each threshold marks a considerable spike in audit intensity and hence should create strong incentives to bunch below the threshold. However, we find no such effect in our large sample analysis. We attribute this empirical observation to optimization costs, particularly to the costs associated with the operational implementation of size management and to information costs. Our paper adds to the emerging field of studies on potential distortions created by threshold-dependent firm regulation. The findings are also relevant for policymakers, as they suggest that the specific design of threshold-dependent policies might allow governments to increase the efficiency of tax audits without distorting the firm size distribution.
Keywords: H26; H32; K42; 340; Tax enforcement; Size-dependent regulation; Bunching; Administrative data; Germany